PEMUTUSAN KONTRAK BISNIS SEBAGAI FORCE MAJEURE AKIBAT BENCANA PANDEMIK COVID 19 - Suherman dan Wicipto Setiadi (Institut agama islam negeri Padangsidimpuan, 2020)
The Indonesian government announced in the middle of March that the spread of Covid 19 was a national disaster. The government also makes policies for citizens to carry out activities at home, such as; study at home, work at home and worship at home this is done in the context of social distancing to break the chain of the spread of Covid 19. The existence of Government policies that implement Large-Scale Social Restrictions (PSBB) policies in several regions in Indonesia, Thus it has a huge impact on the economy in Indonesia, there are many layoffs due to non-production of products and many factories are closed, so that many companies are closed can not carry out their obligations towards contracts that they have signed by other parties. Many business people and the community think that the covid 19 disaster is a force majeure.This type of research is normative-empirical. In normative research, the type of data used is secondary data, which consists of primary legal materials, secondary legal materials and tertiary legal materials. While empirical research, using primary data in the form of answers that can be obtained in the field, namely the companies affected from the covid 19 outbreak.The specific target that will be achieved in this study is to find out whether the covidus 19 disaster is a force majeure on companies that cannot carry out their obligations in the business world in Indonesia.